Civic Online Reasoning Across the Curriculum: Developing and Testing the Efficacy of Digital Literacy Lessons - Sarah McGrew; Joel Breakstone (SAGE Publishing, 2023)
Given the current threat posed by toxic digital content, preparing students to evaluate online sources cannot be relegated to a single subject area-this instruction should happen across the curriculum. This article focuses on materials designed to teach students to evaluate online information across subject areas. ninth-grade biology and world geography teachers taught a series of curriculum-embedded lessons based on the following design principles: (a) Focus on a core question and strategy; (b) engage students in evaluating real online content; (c) feature cognitive apprenticeship and formative assessment; and (d) support teacher learning. We examine whether these lessons helped students become more skilled evaluators of online content. Pretest/posttest data (N =574) showed statistically significant growth in students' ability to evaluate the credibility of online content. We analyze the role played by the curriculum design principles in this interdisciplinary intervention and explore implications for future initiatives.